53 Dr. (12th November 2018) - Crossley, Eleanor; Lawn, Cassie; Groves, Nick; Galloway, Rob
Abstract : 1) Context: In healthcare delivery, serious and critical incidents have demonstrated how human interactions can significantly compromise patient safety. This branch of study known as Human Factors is only recently being taught to healthcare professionals, despite widespread use in aviation and other industries. A local consultant from an NHS teaching hospital introduced one-day Human Factors workshops for multi-disciplinary staff from different NHS Trusts across South-East England. The workshops were free-of-charge for attendees, with over 1000 attendees to date. 2) Issue: Human Factors teaching is still in its infancy; little is known about the effectiveness and transferability of this teaching into healthcare practice. Furthermore, little is known about which teaching methods and content are most powerful and relevant in delivering Human Factors education. 3) Assessment of issue and analysis of its causes: The workshop used incident reports from an NHS teaching hospital to illustrate how failings in Human Factors can contribute to errors in healthcare. It also emphasised that Human Factors teaching is relatively new in medical education; the challenge is therefore to improve staff awareness of Human Factors and its relevance in day-to-day practice. Workshop attendees over a three-month period were therefore asked for their written consent to participate in individual semi-structured telephone interviews following the workshop. Consenting attendees were telephoned by one of two investigators two-to-six months after the workshop, at an agreed date and time. 4) Intervention: Forty-three workshop attendees over a three-month period participated in telephone interviews. Interviewees' key learning points identified five main themes: the importance of effective communication within teams; the need for a change in culture; the role of hierarchy and importance of speaking up; the impact of situational awareness; and the need for more widespread Human Factors education. The qualitative evidence provided by the telephone interviews demonstrated how the workshop enabled individuals to amend their own practice, and also educate colleagues. Numerous specific examples illustrated how attendees had improved patient safety by transferring their learning from the workshop into their individual or team's practices. The lead consultant uses the key learning themes identified by the telephone interviews alongside attendees' written feedback after each workshop to focus the teaching on areas attendees have identified as relevant and transferable to their healthcare practices. 5) Strategy for improvement: This qualitative study uses staff feedback as a proxy measure to demonstrate improved patient safety and outcomes when staff are educated about Human Factors and to understand how attendees incorporate this knowledge into their working environment and relationships with other staff. The Human Factors workshops continue to be delivered to a regional multi-disciplinary audience on approximately a monthly basis. Written feedback continues to record attendees' learning points to ensure the content remains relevant and builds upon the findings of these interviews. A voluntary session at the end of each workshop educates attendees on how to use their learning to teach their colleagues about Human Factors. These sessions allow attendees to incorporate the key learning points of others, as identified by the telephone interviews and written feedback, when delivering their own local Human Factors teaching. 6) Measurement of improvement: The interviews focused on attendees' key learning points from the one-day Human Factors workshop, and asked attendees for specific qualitative evidence if they felt they had transferred their learning into their clinical or non-clinical practice. These interviews were transcribed, coded and themed using framework analysis. 7) Impact: To the best of our knowledge this is the first qualitative study into the transferability of Human Factors education into individuals' healthcare practice. The themes identified by the interviews could be used as a basis to develop future Human Factors curricula. 8) Lessons learnt: Qualitative feedback at a later date to the written feedback on the day of the workshop can further illuminate attendees' learning and the impact of Human Factors education on patient safety. This can help focus the content of further workshops. 9) Message for others: Human Factors teaching can be successfully delivered to multi-disciplinary staff with qualitative evidence of improved patient safety. Workshops can develop local leaders in the field and help to disseminate this new concept to other healthcare staff. The Human Factors workshop powerpoint slides are available free-of-charge to all requesting NHS Trusts.